Effects of Zn addition on the intermetallic formation and joint strength of Sn-3.5Ag-1.0Cu solders / Ramani Mayappan and Iziana Yahya - Mayappan, Ramani; Yahya, Iziana (Penerbit UiTM (UiTM Press), 2025)
The need to replace lead-based solders has received considerable attention among researchers because of their toxicity. The Sn-Ag-Cu family is the most promising candidate. However, these solder systems require some improvement in terms of their performances in terms of mechanical properties. In this study, Sn-3.5Ag-1.0Cu solder was investigated with the addition of 0.1, 0.4 and 0.7 wt.% Zn. The solder was prepared using a powder metallurgy method to form the discs. An intermetallic compound study was conducted by melting a solder disc on a Cu substrate at 250 oC for 1 min. For the shear strength study, the solder was melted at 250 oC on two pieces of the Cu substrate. Aging process was conducted in an oven at 150 oC for 1000 h under an air atmosphere. For the intermetallic study, the aged solder joint was cross-sectioned, mounted in epoxy resin, and observed under a Scanning Electron Microscope. The solder joint specimens were tested using an Instron machine and the fracture surfaces were examined under a Scanning Electron Microscope. The Cu6 Sn5 intermetallic compound was initially formed with scalloped morphology. This intermetallic structure transformed into a flat structure at higher aging temperatures and durations. As aging progressed, another thin and flat intermetallic layer was formed near the Cu interface. The intermetallic compound was identified to be Cu3 Sn. The solder joint strength degraded at a later stage of aging owing to the excessive growth of intermetallics with the 0.7 wt.% exhibit higher values. The fracture mode displays ductile failure at lower aging temperatures and times, but shows brittle failure at higher aging temperatures and longer times.